2012
DOI: 10.2147/ijn.s32391
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatible antifungal acrylic resin containing silver nanoparticles for dentures

Abstract: Background: Inhibition of Candida albicans on denture resins could play a significant role in preventing the development of denture stomatitis. The safety of a new dental material with antifungal properties was analyzed in this work. Methods: Poly(methyl methacrylate) [PMMA] discs and PMMA-silver nanoparticle discs were formulated, with the commercial acrylic resin, Nature-Cryl TM , used as a control. Silver nanoparticles were synthesized and characterized by ultraviolet-visible spectroscopy, dispersive Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 36 publications
(37 reference statements)
2
47
1
2
Order By: Relevance
“…Because of their antimicrobial properties, AgNPs have been added to poly(methyl methacrylate) (PMMA). The results of this study found that PMMA-AgNPs significantly reduced the adherence of C. albicans, while flexural strength of PMMA was decreased (Acosta-Torres et al, 2012;Sodagar et al, 2012). The colonization of the soft lining of denture material by oral fungi could result in infections and stomatitis, and therefore AgNPs were incorporated into composites as antimicrobial agents in order to reduce the microbial colonization of lining materials (Grzegorz et al, 2011;Chladek et al, 2013).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Because of their antimicrobial properties, AgNPs have been added to poly(methyl methacrylate) (PMMA). The results of this study found that PMMA-AgNPs significantly reduced the adherence of C. albicans, while flexural strength of PMMA was decreased (Acosta-Torres et al, 2012;Sodagar et al, 2012). The colonization of the soft lining of denture material by oral fungi could result in infections and stomatitis, and therefore AgNPs were incorporated into composites as antimicrobial agents in order to reduce the microbial colonization of lining materials (Grzegorz et al, 2011;Chladek et al, 2013).…”
Section: Discussionmentioning
confidence: 89%
“…AgNPs were added to composite resins and results demonstrated that, in sufficient concentrations, the presence of nanosilver significantly increased the resins' antibacterial performance (Fan et al, 2011;Ai et al, 2017). Microwave solidification was applied to the denture base preparation after mixing the AgNPs with polymethyl methacrylate (PMMA) powder, and the results showed that the amount of C. albicans attached to the base surface was significantly reduced (Acosta-Torres et al, 2012). AgNPs have also been added to the surface of titanium implants (Massa et al, 2014;Matsubara et al, 2015;Mishra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…All the polyquaternary ammonium salt-containing cements exhibited significant antibacterial activity, accompanied by a reduction of initial compressive strength. Furthermore, it was concluded that the experimental cement is a clinically attractive dental restorative owing to its high mechanical strength and antibacterial functionality [8].…”
Section: Prosthetic Dentistrymentioning
confidence: 99%
“…They also appeared to prevent genotoxic damage to the cells. The authors also claim to have developed a new biocompatible antifungal PMMA denture-based material [8,9].…”
Section: Denture Stomatitismentioning
confidence: 99%
“…The incorporation and deposition of silver nanoparticles on titanium implants and screws were demonstrated effective in preventing bacteria biofilm adhesion and infections (Secinti et al, 2011;Cheng et al, 2013). The use of silver nanoparticles has also been explored for the production of antimicrobial bone graft (Marsich et al, 2013) and in orthodontia, where antifungal acrylic resins containing AgNPs were developed as antifungal compounds for denture bases (Acosta-Torres et al, 2012;Nam et al, 2012;Sodagar et al, 2012). A wide range of silver dressings with broad-spectrum antimicrobial activity is commercially available for topical application and new wound dressing biomaterials have also been proposed in the literature for the management of exuding venous leg ulcers for bioburden and infection reduction (White, 2013;Forlee et al, 2014).…”
Section: Overview Of the Most Promising Applicationsmentioning
confidence: 99%